Investimento estrangeiro direto e remessas de lucros e dividendos do Brasil: estratégia microeconômica e determinantes macroeconômicos (2001-2004) - Mauro Sudano Ribeiro (2006)
The purpose of this thesis is to insert the discussion on profits and dividends repatriations in the context of the Brazilian external accounts analysis, highlighting the importance of data collection, treatment and disclosure of aggregated data on financial flows related to the multinational corporations activity, in the sense of allowing multiple approaches to foreign direct investment financial strategies in the country.Through the utilization of monthly time series and panel data, some of which conceived specifically for this study, and related to the economic activity, to the main financial indicators such as interest rates, foreign exchange rates and inflation indexes, and to the multinational corporations strategic financial decisions, it identifies the mains determinants of profits and dividends repatriations, from 2001 to 2004, under the perspective of the foreign direct investment home countries, and economic activity sectors. The validity of a mixed approach using panel data techniques is proposed and demonstrated, together with recommendations on the relevance of considering such repatriations under a 12-month perspective, consistent with the corporations short and medium-term planning horizon.The contribution includes an evaluation of the profits and dividends repatriation determinants based on the data available from the Foreign Capital in Brazil Census, in its two former editions (1996 and 2001), showing the feasibility of obtaining important results from the accounting information provided by the corporations with foreign participation.